APSH-OP-6: ASSOCIATION BETWEEN THE GUT MICROBIOME AND THEIR METABOLITES WITH HUMAN BLOOD PRESSURE VARIABILITY. (January 2023) - Dinakis, Evany; Nakai, Michael; Gill, Paul; Ribeiro, Rosilene; Yiallourou, Stephanie; Sata, Yusuke; Muir, Jane; Carrington, Melinda; Head, Geoffrey A; Kaye, David M; Marques, Francine Z
Abstract : Objective: Blood pressure (BP) variability is an independent risk factor for cardiovascular events. Recent evidence supports a role for the gut microbiota in BP regulation. However, whether the gut microbiome is associated with BP variability is yet to be determined. Here, we aimed to investigate the interplay between the gut microbiome and their metabolites in relation to three separate parameters of BP variability. Design and method: Ambulatory BP monitoring was performed in 69 participants from two independent sites in Australia (55.1% women; mean ± SD 59.8 ± 7.26-years old, BMI 25.2 ± 2.83 kg/m 2 ). This data was used to determine night-time dipping, morning BP surge (MBPS) and BP variability as standard deviation (SD). The gut microbiome was determined by 16S rRNA sequencing, mRNA expression levels of short-chain fatty acid (SCFA) receptors ( FFAR2, FFAR3 and HCAR2 ) by real-time PCR (qPCR) and metabolite levels by gas chromatography. Results: We identified specific taxa associated with systolic BP variability, night-time dipping and MBPS. Notably, Alistipesfinegoldii and Lactobacillus spp. were only present in participants within the normal ranges of BP variability, MBPS and night-time dipping, while Prevotella spp. and Clostridium spp. were found to be present in extreme dippers and the highest quartiles of BP SD and MBPS. There was a negative association between MBPS and microbial alpha diversity (r = -0.244, P = 0.046). MBPS was also negatively associated with plasma levels of microbial metabolites (SCFAs) (r = -0.305, P = 0.020), particularly acetate (r = -0.311, P = 0.017). We identified a negative correlation between SD data and SCFA receptor FFAR2 mRNA, indicating that participants with higher BP SD had overall lower expression levels of FFAR2 (SD day: r = -0.31, P = 0.039; SD night: r = -0.36, P = 0.016; SD total: r = -0.32, P = 0.035). We also found that participants with a greater percentage in night-time dipping had higher levels of FFAR2 (r = 0.38, P = 0.0087). Conclusions: Gut microbiome diversity, levels of microbial metabolites, and the bacteria Alistipesfinegoldii and Lactobacillus were associated with lower BP variability, whereas a blunted level of SCFA receptor FFAR2 mRNA and Clostridium and Prevotella bacteria were associated with higher BP variability. Our findings suggest the gut microbiome and metabolites may be involved in the regulation of BP variability.